Evolution of anti-SARS-CoV-2 spike protein titers after two-dose of COVID-19 vaccination among people living with HIV - Wang-Da Liu; Man Wai Pang; Jann-Tay Wang; Hsin-Yun Sun; Yu-Shan Huang; Kuan-Yin Lin; Un-In Wu; Guei-Chi Li; Wen-Chun Liu; Yi-Ching Su; Pu-Chi He; Chia-Yi Lin; et al. (Elsevier, 2022)
Background: A community COVID-19 outbreak caused by the B.1.1.7 SARS-CoV-2 variant occurred in Taiwan in May 2021. High-risk populations such as people living with HIV (PLWH) were recommended to receive two doses of COVID-19 vaccines. While SARS-CoV-2 vaccines have demonstrated promising results in general population, real-world information on the serological responses remains limited among PLWH. Methods: PLWH receiving the first dose of SARS-CoV-2 vaccine from 2020 to 2021 were enrolled. Determinations of anti-SARS-CoV-2 spike IgG titers were performed every one to three months, the third dose of the SARS-CoV-2 vaccine or confirmed SARS-CoV-2 infection. All serum samples were tested for anti-nucleocapsid antibody and those tested positive were excluded from analysis. Results: A total of 1189 PLWH were enrolled: 829 (69.7%) receiving two doses of the AZD1222 vaccine, 232 (19.5%) of the mRNA-1273 vaccine, and 128 (10.8%) of the BNT162b2 vaccine. At all time-points, PLWH receiving two doses of mRNA vaccines had consistently higher antibody levels than those receiving the AZD1222 vaccine (p <0.001 for all time-point comparisons). Factors associated with failure to achieve an anti-spike IgG titer >141 BAU/mL within 12 weeks, included type 2 diabetes mellitus (DM) (adjusted odds ratio [aOR], 2.24; 95% CI, 1.25-4), a CD4 T cell count <200 cells/mm3 upon receipt of the first dose of vaccination (aOR, 3.43; 95% CI, 1.31-9) and two homologous AZD1222 vaccinations (aOR, 16.85; 95%CI, 10.13-28). For those receiving two doses of mRNA vaccines, factors associated with failure to achieve an anti-spike IgG titer >899 BAU/mL within 12 weeks were a CD4 T cell count <200 cells/mm3 on first-dose vaccination (aOR, 3.95; 95% CI, 1.08-14.42) and dual BNT162b2 vaccination (aOR, 4.21; 95% CI, 2.57-6.89). Conclusions: Two doses of homologous mRNA vaccination achieved significantly higher serological responses than vaccination with AZD1222 among PLWH. Those with CD4 T cell counts <200 cells/mm3 and DM had consistently lower serological responses.